Listen and make room : joining God in welcoming children - Shank, Harold (Abilene Christian University Press, 2020)
"When Jesus made room, the vulnerable came for prayer. He treated their ills. He fixed what was broken. Jesus gave sight to the blind, made the lame walk, and welcomed the little children, creating space for those who had been excluded. Then he listened to those who often had no voice. Today, those people are often children. Finding places for those who are left out, especially children, is the work of discipleship. We rarely listen to those who have small voices in our world. Instead, we fill up all the space ourselves, leaving no room for those who have little ability to acquire a spot. But Listen and Make Room shows us that to follow Jesus's example means to understand that the vulnerable are at the core of God's mission"--